2012
DOI: 10.1038/bjc.2012.330
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-126 induces angiogenesis and lymphangiogenesis by activation of VEGF-A in oral cancer

Abstract: Background:MicroRNA (miRNA)-126 (miR-126) is an endothelial-specific miRNA located within intron 7 of epidermal growth factor-like domain 7 (EGFL7). However, the role of miR-126 in cancer is controversial.Methods:We examined the function of miR-126 in oral squamous cell carcinoma (OSCC) cells. Furthermore, a series of 118 cases with OSCC were evaluated for the expression levels of miR-126.Results:MicroRNA-126 (miR-126) was associated with cell growth and regulation of vascular endothelial growth factor-A activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(122 citation statements)
references
References 49 publications
6
116
0
Order By: Relevance
“…For example, miRNA (miR)-126, originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [9][10][11] has been shown to function as a critical tumor suppressor in various types of solid tumors. 5,[12][13][14][15][16][17][18][19] In contrast, we have shown that miR-126 is aberrantly overexpressed and likely plays an oncogenic role in core binding factor (CBF) leukemia. 20 CBF leukemia is characterized by the presence of a t(8;21)(q22;q22) or an inv(16)(p13.1q22) chromosomal rearrangement, which accounts for ;20% to 30% of primary acute myeloid leukemia (AML) cases.…”
Section: Key Pointsmentioning
confidence: 88%
“…For example, miRNA (miR)-126, originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [9][10][11] has been shown to function as a critical tumor suppressor in various types of solid tumors. 5,[12][13][14][15][16][17][18][19] In contrast, we have shown that miR-126 is aberrantly overexpressed and likely plays an oncogenic role in core binding factor (CBF) leukemia. 20 CBF leukemia is characterized by the presence of a t(8;21)(q22;q22) or an inv(16)(p13.1q22) chromosomal rearrangement, which accounts for ;20% to 30% of primary acute myeloid leukemia (AML) cases.…”
Section: Key Pointsmentioning
confidence: 88%
“…OSCC often leads to dysfunctions of chewing, swallowing, speech as well as the loss of esthetics. What's more, although there are more than 80% of early-stage OSCC patients that can be cured by therapy, there are still about 70% of patients with progressive disease cannot be cured [4]. Consequently, it is urgently needed for precise early detection of OSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several online databases are available to identify potential miRNA targets. Analysis preformed using the PicTar algorithm (http://www.pictar.org/) (20), miRBase (www.mirbase.org) (21) and TargetScan target prediction (version 6.2; www.targetscan.org) (22) tools revealed that VEGF was the putative target of miR-126 that may serve a role in angiogenesis owing to regulation of VEGF signaling (23,24). Alteration of expression of miR-126 was also reported in various breast, lung and prostate cancer cells (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%